Falling through the cracks : young adults’ recollections of exposure to domestic violence during childhood - Warwick, Danelia; Van der Westhuizen, Marichen; Alpaslan, Nicky (Social Work/Maatskaplike Werk, 2019)
Exposure to domestic violence during childhood impacts on the child’s overall development in a way that affects functioning in adulthood (cf. Rzepka, 2007:2; Bogeanu, 2012). This article seeks to describe the recollections of young adults who were exposed to domestic violence, so as to develop an understanding of what is needed to develop effective services to child victims of domestic violence. The description is based on a qualitative research study that confirmed a lack of services to children exposed to domestic violence. The participants described the influence on their childhood and on their current lives, and made suggestions for social work servicesMs Danelia Warnick, Social worker; Department of Social Development and former master’s student in the Department of Social Work, University of South Africa, Pretoria, South Africa.